First record of marine goby Priolepis profunda (Weber, 1909) (Teleostei: Gobiidae) from Taiwan - Harefa, Tonisman; Chen, I-Shiung (Zootaxa, 2024)
The marine goby Priolepis profunda (Weber, 1909) is recorded for the first time from Taiwan, based on three specimens (33.2–36.4 mm SL) collected from fishery by-catches of commercial trawling that landed at Da-shi fish port in Ilan County and Keziliao fishing harbor in Kaohsiung, Taiwan. The redescription of current newly recorded species would be provided in this paper.